Impact of the Covid 19 Pandemic on the Quality of Good Local Government Governance in Indonesia - Khairudin Khairudin (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2025)
The aim of this research is to assess the impact of the Covid-19 pandemic on the quality of good local government governance. This study involved all provincial governments in Indonesia with observation years 2019 and 2020. The assessment of the quality of good regional governance was measured using the Principal Component Analysis method. The test was carried out by comparing the value of the good regional governance index in the year before the Covid-19 outbreak with the value of the good regional governance index in the year of the Covid-19 outbreak. The findings showed that the governance index of all provincial governments in 2020 decreased by an average of 0.68 points or 10.82% so that the Covid-19 Pandemic in Indonesia has reduced the quality of regional governance. Therefore, all stakeholders need to be more serious in building the principles of good governance from planning to control to maintain quality, even in crisis situations.